Mercury stress tolerance in wheat and maize is achieved by lignin accumulation controlled by nitric oxide. (15th August 2022) - Shao, Ruixin; Zhang, Junjie; Shi, Weiyu; Wang, Yongchao; Tang, Yulou; Liu, Zikai; Sun, Wei; Wang, Hao; Guo, Jiameng; Meng, Yanjun; Kang, Guozhang; Jagadish, Krishna SV; et al.
Abstract: Nitric oxide (NO) is an important phytohormone for plant adaptation to mercury (Hg) stress. The effect of Hg on lignin synthesis, NO production in leaf, sheath and root and their relationship were investigated in two members of the grass family - wheat and maize. Hg stress decreased growth and lignin contents, significantly affected phenylpropanoid and monolignol pathways (PAL, phenylalanine ammonia-lyase; 4-coumarate: CoA ligase, 4CL; cinnamyl alcohol dehydrogenase, CAD), with maize identified to be more sensitive to Hg stress than wheat. Among the tissue types, sheath encountered severe damage compared to leaves and roots. Hg translocation in maize was about twice that in wheat. Interestingly, total NO produced under Hg stress was significantly decreased compared to control, with maximum reduction of 43.4% and 42.9% in wheat and maize sheath, respectively. Regression analysis between lignin and NO contents or the activities of three enzymes including CAD, 4CL and PAL displayed the importance of NO contents, CAD, 4CL and PAL for lignin synthesis. Further, the gene expression profiles encoding CAD, 4CL and PAL provided support for the damaging effect of Hg on wheat sheath, and maize shoot. To validate NO potential to mitigate Hg toxicity in maize and wheat, NO donor and NO synthase inhibitor were supplemented along with Hg. The resulting phenotype, histochemical analysis and lignin contents showed that NO mitigated Hg toxicity by improving growth and lignin synthesis and accumulation. In summary, Hg sensitivity was higher in maize seedlings compared to wheat, which was associated with the lower lignin contents and reduced NO contents. External supplementation of NO is proposed as a sustainable approach to mitigate Hg toxicity in maize and wheat. Graphical abstract: Image 1 Highlights: Hg inhibited growth and lignin synthesis of two food crops. Maize seedlings were identified to be more sensitive to Hg stress than wheat. The sheath of wheat, and shoot of maize encountered severe damage under Hg stress. Hg significantly decreased the nitric oxide content in sensitive parts of wheat and maize. Nitric oxide could mitigate Hg toxicity in maize and wheat.